(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
إن نظام التضميم بتقسيم التردد التعامدي (Orthogonal Frequency Division Multiplexing (OFDM) بدون ترميز قناة يكون عرضة لخفوت متعدد المسارات، حيث تصل كل الحوامل الجزئية عند المستقبل بطويلات مختلفة. وباستعمال ترميز فوق الحوامل الجزئية فمن الممكن كسب تنوع في التردد، وبالتالي زيادة القدرة على كشف ترميز حتى للحوامل الجزئية الضعيفة. لذلك يتم اختيار ترميز تربو الذي ينتمي لمجموعة ترميزات القناة ليطبّق بنظام(OFDM). أقترح بهذا البحث تقديم نظام مكوّن من خوارزمية مثلى من حيث السرعة يطبّق فيها ترميز تربو بنظم التضميم بتقسيم التردد التعامدي (OFDM) للتخفيف من الخفوت بهذه النظم وحساب نسبة خطأ البت أو الحزمة ) BER) (FER/ (Bit / Frame error rate، مع شرح خطوات خوارزمية النظام. ويتم إيجاد بترميز تربو كلّ من خوارزمية عملية الترميز وخوارزمية مشذّر عشوائي مع برمجياتهما. واستعملت خوارزمية Max-Log-MAP المقترحة سابقاً لكشف الترميز. ويتم دراسة تأثير الوسطاء الداخلية لترميز تربو ( حدودية الترميز، عدد تكرارات كشف الترميز، طول صندوق المعلومات، نسبة الترميز) في أداء ترميز تربو بهذا النظام في قناة ضجيج غاوس الأبيض الجمعي (Additive white Gaussian noise(AWGN)) كأمثلة تطبيقية لهذا النظام المقترح. The bit error rates of orthogonal frequency division multiplexing (OFDM) system are not acceptable without a powerful channel coding scheme, especially in fading channels. The reason for this is the lack of frequency diversity. In multi carrier systems like (OFDM), some sub carriers may be completely lost because of deep fades. Thus, using turbo coding across the sub carriers, errors of weak sub carriers can be corrected, where turbo code belongs to set of channel codes. This research presents an optimal algorithm using turbo code with( OFDM) system, for simulate bit/ frame error rate( BER /FER) performance of the turbo coded OFDM system, and studies the influence of code internal parameters on the performance of turbo code. I present in turbo code: encoding algorithm, random interleaver algorithm, and use Max-Log-MAP algorithm for decoding. Finally, I show in this research the practical programs for (algorithm of turbo encoding, random interleaver algorithm).